2008
DOI: 10.1007/s00580-008-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

Reference biochemical values for three cultured Sparid fish: striped sea bream, Lithognathus mormyrus; common dentex, Dentex dentex; and gilthead sea bream, Sparus aurata

Abstract: The aim of the present study was to set up reference intervals for biochemical parameters in new candidate species of Mediterranean marine fish culturestriped sea bream, Lithognathus mormyrus and common dentex, Dentex dentex as well as traditionally cultured species-gilthead sea bream, Sparus aurata. The reference biochemical values were assessed for plasma cortisol, glucose, Ca, inorganic P, Na, K, Cl, C-reactive protein, hematocrit, and prothrombin time. The biochemical reference values established may allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…1). Glucose levels, besides following the same trend as cortisol levels, are, in general, below the basal values for this species [45]. This could be related to the fish's inability to maintain the same levels of glucose in the blood due to the high demand for glucose mobilization to other tissues.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…1). Glucose levels, besides following the same trend as cortisol levels, are, in general, below the basal values for this species [45]. This could be related to the fish's inability to maintain the same levels of glucose in the blood due to the high demand for glucose mobilization to other tissues.…”
Section: Discussionmentioning
confidence: 73%
“…coping styles, cognitive perception) [39,43,44]. Additionally, values registered for control fish, in every trial, are higher than the reference values reported in the literature for this species [45]. These discrepancies may have several causes, which is why cortisol should be used with caution when evaluating the magnitude of the stress response.…”
Section: Discussionmentioning
confidence: 85%
“…Standard reference intervals have been established for some fish species, such as gilthead sea bream, European sea bass, dojo loach, Amur sturgeon and skipjack, yellowfin and bluefin tuna (Svoboda et al 2001;De Pedro et al 2005;Coz-Rakovac et al 2005;Knowles et al 2006;Tavares-Dias and Moraes 2007;Zhou et al 2009;Cao and Wang 2010;Di Marco et al 2011;Peres et al 2013). A scarce number of studies on haematological and biochemical parameters were conducted in sparid fish species, including gilthead sea bream (Sparus aurata) (Yildiz 2009;Peres et al 2013;Fazio et al 2013) common dentex (Dentex dentex) (Yildiz 2009), striped sea bream (Lithognathus mormyrus) (Yildiz 2009), saddled bream (Oblada melanura) (Ferri et al 2011), yellowfin sea bream (Acanthopagrus latus) (Karimi et al 2013;Akbari 2014) and black sea bream (Acanthopagrus schlegeli) (Chang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated in this study by the levels of plasma glucose registered in the fish from all trials (Fig.1). Glucose levels, besides following the same trend as cortisol levels, are, in general, below the basal values for this species (45). This could be related to the fish's inability to maintain the same levels of glucose in the blood due to the high demand for glucose mobilization to other tissues.…”
Section: Discussionmentioning
confidence: 73%
“…coping styles, cognitive perception) (39,43,44). Additionally, values registered for control fish, in every trial, are higher than the reference values reported in the literature for this species (45). These discrepancies can have several causes and that is the reason why cortisol should be used with caution when evaluating the magnitude of the stress response.…”
Section: Discussionmentioning
confidence: 86%